Propuesta basada en las Tics, para mejorar capacidades terminales, de estudiantes universitarios de Ingeniería de Minas, sede UNT Huamachuco, 2018 - Hernandez Vasquez, Jose Javier (2019)
ABSTRACT The objective of this research is the application of the proposal based on the use of ICTs for the development of the terminal skills of engineering and mining students at the Huamachuco headquarters of the UNT in pre-professional practice. The study was carried out with the students of VIII and X cycle of the Faculty of Mining Engineering, taking into account three dimensions of terminal skills, such as problem detection, planning and propose solutions, for which it was elaborated and it validated the information collection instruments, which are an observation guide and a checklist, the same ones that were used both as pre-test and post-test in the pre-experimental research. The population was finite and formed by the students of the VIII and X cycle of the faculty of mining engineering, with the population and shows a total of 60 students, constituted in a single experimental group. The pre-experimental design was used for the testing of hypotheses, for which ten learning sessions were developed, with a duration of 2 pedagogical hours for each of them. The results obtained when applying the research corroborated that the didactic proposal did significantly influence the development of students' abilities, as confirmed by the statistical test in the general evaluation of the test in its respective dimension, whose p value in the T student test is less than 0.05 (p = 0.000 < 0.05). In conclusion, we affirm that the students of Mining Engineering of the National University of Trujillo, based in Huamachuco, developed their capacities in a significant way in terms of problem detection, planning and problem solving, using ICTs.